Emotions and Sport Management: A Bibliometric Overview - Baier-Fuentes, Hugo; González-Serrano, María Huertas; Alonso-Dos Santos, Manuel; Inzunza-Mendoza, Williams; Pozo-Estrada, Victor (Frontiers in Psychology, 2020)
Emotions are considered a fundamental aspect of sport scenarios, and within sports, consumer behavior is a very popular area of research in the sport management field. Thus, in recent years, there has been a growing interest for sport managers regarding the role that emotions play in sport consumer behavior. Thus, the aim of this paper is to provide an overview of the academic research on emotions in the sport management field using two techniques: a bibliometric performance analysis and a graphic mapping of the references in this field. This analysis focuses on authors, journals, papers, institutions and countries. Bibliometric indicators including the h-index measure, productivity and the number of citations were used to perform the performance analysis. Then, VOSviewer software was used to perform co-citation, bibliographic coupling and co-occurrence of keyword analysis (mapping analysis). The results of both types of analysis are consistent, with the USA being the most influential country in emotions in sport management research because the main authors and institutions in this research field belong to this country. The overall results indicate that the literature on this research topic has grown significantly in recent years in all scientific disciplines; however, the research topic is incipient, and therefore, the number of articles is still limited. Thus, this research presents the key aspects in the topic of emotions in sport management that could be helpful for researchers and policy makers in the field of sport management to make future decisions.